Correlation of Lower Limb Muscles and Body Mass Index with Body Balance in the Elderly - Valentina, Natasya; Kurniawati, Patricia M; Maramis, Margarita M (Folia Medica Indonesiana, 2019)
Indonesia enters the ageing population because of increasing elderly population. The large number of ederly population can have negative impact if they have some problems, such as increased disability and increased rates of life dependence. Based on health research, it was mentioned that the cause of the most injuries to the elderly group is falls that are caused by balance disorder. Balance problems can be caused by changes of musculoskeletal function. In addition, Body Mass Index (BMI) is still a problem that often occurs in the elderly that can affect daily activities. The objective of this study was to prove that lower limb muscle strength and BMI have correlation with body balance in the elderly. This study used a cross-sectional method carried out on individuals from affordable populations with Kendall Tau C data analysis. Thirty-nine respondents were selected based on inclusion and exclusion criteria. Data were taken from these respondents on weight and height measurement for BMI, size of lower limb muscle strength using a leg dynamometer, and body balance based on risk of falls using Berg's balance scale. We obtained significant score 0,000 for correlation between lower limb muscle strength with body balance in elderly, and correlation between BMI with body balance in elderly. In conclusion, there is strong positive correlation between lower limb muscle strength with body balance in elderly. It is shown by the better muscle strength; the risk of falling in the elderly is getting lower. There is strong positive correlation between BMI with body balance in elderly. It is shown by increasing BMI away from normal scale; the risk of falling is higher.